Analysis Of Relationship Development Of Online Dating Application Users In Looking For A Life Partner (Phnomenological Study Of Women Using Online Dating Applications In Jakarta) - Marghaputra, Putu Arindya Laksmidewi (UNIVERSITAS PAKUAN, 2023)
The development of digital technology has changed the way people communicate. With the advancement of technology, online dating is becoming a thing. Three women who use a dating app were interviewed for this qualitative study. By revealing oneself through a dating app, the researchers hope to gain a better knowledge of the process of relationship growth experienced by the participants. Self-disclosure theory, social penetration theory, and computer-mediated communication were used as references in this study (CMC). This study uses the phenomenological method to explore individual knowledge in the construction of meanings and concepts connected to the process of developing relationships with targeted partners through computer-mediated communication (CMC). The findings show that online dating app users increasingly reveal themselves to possible partners, with the depth of self-disclosure increasing in tandem with relationship intimacy.